Expression of genes that regulate follicle development and maturation during ovarian stimulation in poor responders. Issue 1 (January 2021) - Vaitsopoulou, Christine I.; Kolibianakis, Efstratios M.; Bosdou, Julia K.; Neofytou, Eirini; Lymperi, Stefania; Makedos, Anastasios; Savvaidou, Despina; Chatzimeletiou, Katerina; Grimbizis, Grigoris F.; Lambropoulos, Alexandros; Tarlatzis, Basil C.
Abstract: Research question: Sex hormone-binding globulin ( SHBG ), androgen receptor ( AR ), LH beta polypeptide ( LHB ), progesterone receptor membrane component 1 ( PGRMC1 ) and progesterone receptor membrane component 2 ( PGRMC2 ) regulate follicle development and maturation. Their mRNA expression was assessed in peripheral blood mononuclear cells (PBMC) of normal and poor responders, during ovarian stimulation. Design: Fifty-two normal responders and 15 poor responders according to the Bologna criteria were enrolled for IVF and intracytoplasmic sperm injection and stimulated with 200 IU of follitrophin alpha and gonadotrophin-releasing hormone antagonist. HCG was administered for final oocyte maturation. On days 1, 6 and 10 of stimulation, blood samples were obtained, serum hormone levels were measured, RNA was extracted from PBMC and real-time polymerase chain reaction was carried out to identify the mRNA levels. Relative mRNA expression of each gene was calculated by the comparative 2 −DDCt method. Results: Differences between mRNA levels of each gene on the same time point between the two groups were not significant. PGRMC1 and PGRMC2 mRNA levels were downregulated, adjusted for ovarian response and age. Positive correlations between PGRMC1 and AR (standardized beta = 0.890, P < 0.001) from day 1 to 6 and PGRMC1 and LHB (standardized beta = 0.806, P < 0.001) from day 1 to 10 were found in poor responders. PGRMC1 and PGRMC2 were positively correlated on days 6 and 10 in normal responders. Conclusions: PGRMC1 and PGRMC2 mRNA are significantly decreased during ovarian stimulation, with some potential differences between normal and poor responders.